Extremophiles for microbial-electrochemistry applications: A critical review. (May 2018) - Shrestha, Namita; Chilkoor, Govinda; Vemuri, Bhuvan; Rathinam, Navanietha; Sani, Rajesh K.; Gadhamshetty, Venkataramana
Highlights: Halophiles survive hypersaline conditions in MESs. Thermophiles survive hot conditions in MESs. Extremophiles exhibit higher enzyme expression activity. Extremophiles exhibit diverse electron transfer mechanisms. Abstract: Extremophiles, notably archaea and bacteria, offer a good platform for treating industrial waste streams that were previously perceived as hostile to the model organisms in microbial electrochemical systems (MESs). Here we present a critical overview of the fundamental and applied biology aspects of halophiles and thermophiles in MESs. The current study suggests that extremophiles enable the MES operations under a seemingly harsh conditions imposed by the physical (pressure, radiation, and temperature) and geochemical extremes (oxygen levels, pH, and salinity). We highlight a need to identify the underpinning mechanisms that define the exceptional electrocatalytic performance of extremophiles in MESs.